Soluções numéricas para um modelo de secagem da banana via método de diferenças finitas - Silva, Guilherme da Cunha e (Universidade Federal de São Carlos, 2022)
Since banana is a food of high energy value, has low production technological indexes and has great socioeconomic importance for Brazil, the increase in shelf life is desired. Drying is one of the most used processes in conservation and maintenance of its guarantees, whose main objective is the quality of a product with longer shelf life, post- processing refrigeration exemption and shorter enzymatic and oxidative degradation. On the other hand, for the dimensioning of equipments and optimal process control, is required a clear understanding of the transport phenomena, heat and mass transfer, the properties involved and the correct choice of the numerical method for solving the equations derived from the discretization. In this sense, two numerical methods were developed and studied, Progressive Finite Difference Method and Method of Lines, in order to study the transfers. Simulations in Octave Software were performed in order to check the convergence order of the method applied to a simplified problem.
Numerical solutions for a banana drying model by finite difference method
Keywords: Banana; Secagem; Diferenças Finitas; Estabilidade; Convergência; Banana; Drying; Finite Differences; Stability; Convergence; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS::INSTALACOES INDUSTRIAIS DE PRODUCAO DE ALIMENTOS